Onset of respiratory symptoms among Chinese students: associations with dampness and redecoration, PM10, NO2, SO2 and inadequate ventilation in the school. (3rd May 2020) - Li, Tian; Zhang, Xin; Li, Chenghuan; Bai, Xu; Zhao, Zhuohui; Norback, Dan
Abstract: Objective: To study onset of respiratory symptoms among students in China in relation to the school and the home environment. Methods: A two-year prospective cohort study among 1325 students in eight schools. Air pollution was measured at baseline in the schools. Respiratory symptoms and the home environment were assessed by a questionnaire. Results: The 2-year onset was 14.3%, 23.2%, 15.4%, 4.7% and 37.3% for wheeze, daytime attacks of breathlessness, nocturnal cough, nocturnal wheeze/breathlessness and respiratory infections, respectively. The mean concentrations of PM10, SO2, NO2, ozone and CO2 in the classrooms were 129 µg/m 3, 68.0 µg/m 3, 43.2 µg/m 3, 8.6 µg/m 3 and 1208 ppm, respectively. Environmental tobacco smoke (ETS), dampness/mold at home and ozone in the classroom were associated with onset of wheeze. Onset of daytime breathlessness was associated with redecoration and dampness/mold at home and CO2 and relative air humidity (RH) in the classrooms. Dampness/mold at home, PM10, CO2 and RH in the classrooms and outdoor PM10, SO2 and NO2 were associated with onset of nocturnal cough. Onset of nocturnal wheeze/breathlessness was associated with dampness/mold at home and RH and PM10 in the classrooms. Respiratory infections were more common at higher levels of outdoor PM10 . Conclusions: Air pollution (PM10, ozone, SO2 and NO2 ) and inadequate ventilation flow in the classrooms (indicated by CO2  > 1000 ppm) and ETS, dampness or mold and chemical emissions from redecoration at home can increase onset of respiratory symptoms.